WOMEN’S LANGUAGE FEATURES OF THE MAIN FEMALE CHARACTER IN HARPER LEE’S TO KILL A MOCKINGBIRD - Aisyah Aulia Tahir; Murni Mahmud; Yunitari Mustikawati (ELITERATE : Journal of English Linguistics and Literature Studies, 2022)
This research aims to find out the women’s language features that used by the main female character in “To Kill a Mockingbird Novel 1960” using Lakoff’s theory (1975) Women’s Language theory. The research will also describe how the main female character expressed every sentence that has women’s language features with stylisctic analysis and show the situation in the sentence with Hyme’s (1974) Speaking theory. The descriptive analytics approach was applied in this research to characterize the aspects and qualities of the subject. The research findings show that lexical hedges or fillers, tag question, rising intonation on declaratives, empty adjective, emphatic emphasis, superpolite form, hypercorrect grammar, avoidance of powerful swear words, and intensifier are nine features of women's language used by the main female character. The researcher also finds how the main female character expressed her sentences with linguistic deviation and literary analysis. And the researcher discovers 8 elements of situation that happened in the conversation, namely setting, participant, ends (goal), act sequence, key, instrumentalities, norms of interaction, and genre. The research was able to identify the women's language features and define how they are communicated as well as the situation in the conversation as a conclusion.